(3fRgI GdfGXQ hHgLI GdNGWQs - (3Ydj Hf eMeO Hf NGdO GdHdGWfSj GdTGej GdTGaYj,J (B936 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj SejJ gPG(B: (3fRgI GdfGXQ hHgLI GdNGWQ, hChOYf aj ChQGbg CfhGYkG ef afhf CUfGagG JSJMdj, s
(3BNQgG (B:s
(3hdHGH ehdGg GdcQje edGRe hjeG jQhe ef GdebGUO jLfM s
(3HChdgG agQS dehVhYGJ GdcJGHs
(3hGdfSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B11 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B743s
Keywords: (3GdCOHs